2016
DOI: 10.1186/s12967-016-0792-1
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells and their secreted molecules predominantly ameliorate fulminant hepatic failure and chronic liver fibrosis in mice respectively

Abstract: BackgroundOrthotopic liver transplantation is the only effective treatment for liver failure but limited with shortage of available donor organs. Recent studies show promising results of mesenchymal stem cells (MSCs)-based therapies.MethodsWe systematically investigate the therapeutic effects of MSCs or MSC-conditioned medium (MSC-CM) in ameliorating fulminant hepatic failure (FHF) and chronic liver fibrosis in mice. In addition, extensive flow cytometry analysis of spleens from vehicle and MSC- and MSC-CM-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
138
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 31 publications
7
138
0
Order By: Relevance
“…58 Similar results were obtained when MSC-conditioned media (MSC-CM) were applied instead, 58, 59 which suggests that MSCs might achieve a therapeutic effect in vivo via their secreted EVs, such as exosomes.…”
Section: Therapeutic Properties Of Msc-derived Exosomes On Liver Diseasementioning
confidence: 72%
“…58 Similar results were obtained when MSC-conditioned media (MSC-CM) were applied instead, 58, 59 which suggests that MSCs might achieve a therapeutic effect in vivo via their secreted EVs, such as exosomes.…”
Section: Therapeutic Properties Of Msc-derived Exosomes On Liver Diseasementioning
confidence: 72%
“…They also observed marked reduction in mononuclear leukocytic infiltration, prevention of hepatocyte apoptosis and inhibition of bile duct duplication after MSC-CM treatment. Huang et al [65] also found that MSC and MSC-CM infusion similarly stimulated liver regeneration and suppressed hepatocelluar death in mice with acute and chronic liver failure.…”
Section: Discussionmentioning
confidence: 92%
“…Strong positive α-SMA immune-reaction was observed in the wall of the central vein and in-between the hepatocytes in CCL4 treated group. Cheung et al [47] mentioned that, α -SMA is a marker for the activity of hepatic stellate cells (HpSCs), which are the primary cell type that mediate fibrogenesis. In response to inflammation, HpSCs are activated into myofibroblasts and proliferated by the action of TGFb and PDGF, respectively, secreted by macrophages [44,45] .…”
Section: Discussionmentioning
confidence: 99%
“…Although statistically insignificant, secretome treatment also reduced the cell viability of HSCs, suggestive of anti-fibrogenic effects of secretome itself. Indeed, several studies have reported the antifibrogenic effects of mesenchymal stem cells or their secretome in the model of liver fibrosis [37][38][39][40][41][42]. Since liver fibrosis process is initiated by inflammation, it appears that secretome reduces the viability of HSCs through anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%